2014
DOI: 10.3897/natureconservation.7.6890
|View full text |Cite
|
Sign up to set email alerts
|

Estimating population size of a nocturnal burrow-nesting seabird using acoustic monitoring and habitat mapping

Abstract: Estimating population size of a nocturnal burrow-nesting seabird using acoustic monitoring and habitat mapping. Nature Conservation 7: 1-13. doi: 10.3897/natureconservation.7.6890 Abstract Population size assessments for nocturnal burrow-nesting seabirds are logistically challenging because these species are active in colonies only during darkness and often nest on remote islands where manual inspections of breeding burrows are not feasible. Many seabird species are highly vocal, and recent technological innov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(97 citation statements)
references
References 39 publications
3
91
1
2
Order By: Relevance
“…Several previous studies in closely related procellariforms, with similar call amplitudes and breeding habitats, found that Wildlife Acoustic's Song Meter units can record vocalizations up to 50 m away (Buxton & Jones , Oppel et al . , Dufour et al . ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies in closely related procellariforms, with similar call amplitudes and breeding habitats, found that Wildlife Acoustic's Song Meter units can record vocalizations up to 50 m away (Buxton & Jones , Oppel et al . , Dufour et al . ).…”
Section: Methodsmentioning
confidence: 99%
“…The importance of controlling for these factors that affect the soundscape, and the detectability of a species’ vocalizations, has been discussed in detail in the literature (Buxton & Jones , Oppel et al . ) and should be considered when studying biophony within a soundscape.…”
mentioning
confidence: 99%
“…This translates to a 19% reduction in standard errors around the mean and an increase in statistical power equivalent to increasing a survey's sample size (n) by a factor of 1.52, i.e., (1-0.19) -2 , assuming samples are truly independent of one another. Given call rates (and other similar measures of vocal activity) are often used as indices of abundance (Sepúlveda et al 2006, Borker et al 2014, Oppel et al 2014 greater statistical power will translate into an enhanced ability to detect differences in abundance between two different places or across different years. This is of particular importance for scientists attempting to understand ecological processes and conservation practitioners whose management Fig.…”
Section: Reduction Of Variability Between Samplesmentioning
confidence: 99%
“…This study adds to the growing utility of off-the shelf automated recording systems such as Wildlife Acoustics SM2 recorders which include long-term monitoring of vocal behaviour (Bruni and Foote 2014), estimating population size (Oppel et al 2014), calculations of species richness (Haselmayer and Quinn 2000), species at risk monitoring (Holmes et al 2014) and the ability to localize sounds (Mennill et al 2012). Information about individuals obtained from automated recordings will provide important insights in the study of behaviour and conservation of species, particularly those more sensitive to human disturbance.…”
Section: Discussionmentioning
confidence: 98%